ANALYSIS OF ANTECEDENTS OF PURCHASE DECISIONS FOR SAMSUNG SMARTPHONES AT THE CILILITAN WHOLESALE CENTER (PGC) - Amaral, Millenia Christina; Perkasa, Didin Hikmah; Abdullah, Muhammad Al Faruq (Jurnal Manajemen dan Bisnis Madani, 2025)
This research aims to determine the influence of E-Wom (Electronic World of Mouth), Product Quality and Brand Ambassadors on Purchase Decisions. The approach that researchers used in this research was quantitative. The population in this study were visitors to the Cililitan Wholesale Market Mall, 3rd floor. The sampling technique used in this study used the Hair formula because the population size was not known with certainty. The data collection method uses analysis techniques using SEM (Structural Equational Modeling) which includes inner model and outer model tests and the tool used is SmartPLS 3.0. The data collection technique uses a questionnaire whose validity and reliability have been tested. The research results show that the Electronic Word of Mouth variable on Purchase Decisions has no significant effect. Meanwhile, Product Quality and Brand Ambassador have a positive and significant influence on Purchase Decisions. Keywords : Electronic Word of Mouth, Product Quality, Brand Ambassador, Purchase Decision